The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1016/j.physbeh.2009.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone, facial symmetry and cooperation in the prisoners' dilemma

Abstract: Recent research has analyzed how individual characteristics, like the exposure to different hormones and symmetry, affect decision-making and strategic behaviour. The present article investigates the effect of symmetry, of exposure to testosterone (T) in utero and during puberty and of current T on cooperation in a Prisoners' Dilemma Game (PDG). T is a hormone with well known effect on males' behaviour, and that promotes activities that seek to increase reproductive success. Fluctuating Asymmetry (FA) reflects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
63
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 81 publications
6
63
0
2
Order By: Relevance
“…Development or examination of accurate but more applicable methods of measuring hormonal levels can help researchers assess the robustness of our findings related to the biology of risk and time preferences. (Bröder & Hohmann, 2003;Burns, 2006;Buser, 2010;Buser, 2011;Chen et al, 2009;Da Silva et al, 2011;Pearson & Schipper, 2011;Schipper, 2011a;Wozniak et al, 2011) Indirect measures of prenatal exposure to hormones (D2:D4 ratio) (N=19) (Apicella et al, 2008;Apicella et al, 2011;Brañas-Garza & Rustichini, 2011;Buser, 2011;Coates & Page, 2009;Da Silva et al, 2011;Dreber & Hoffman, 2007;Garbarino et al, 2011;Guiso & Rustichini, 2011;Millet & Dewitte, 2006;Millet & Dewitte, 2008;Millet & Dewitte, 2009;Pearson & Schipper, 2012;Sanchez-Pages & Turiegano, 2010;Sapienza et al, 2009;Schipper, 2011a;Trahms et al, 2010;van den Bergh & Dewitte, 2006) Direct measures of hormones (saliva or blood samples) (N=11) (Apicella et al, 2008;Apicella et al, 2011;Burnham, 2007;Coates & Herbert, 2008;Sanchez-Pages & Turiegano, 2010;Sapienza et al, 2009;Schipper, 2011a;Schipper, 2011b;White et al, 2006;…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Development or examination of accurate but more applicable methods of measuring hormonal levels can help researchers assess the robustness of our findings related to the biology of risk and time preferences. (Bröder & Hohmann, 2003;Burns, 2006;Buser, 2010;Buser, 2011;Chen et al, 2009;Da Silva et al, 2011;Pearson & Schipper, 2011;Schipper, 2011a;Wozniak et al, 2011) Indirect measures of prenatal exposure to hormones (D2:D4 ratio) (N=19) (Apicella et al, 2008;Apicella et al, 2011;Brañas-Garza & Rustichini, 2011;Buser, 2011;Coates & Page, 2009;Da Silva et al, 2011;Dreber & Hoffman, 2007;Garbarino et al, 2011;Guiso & Rustichini, 2011;Millet & Dewitte, 2006;Millet & Dewitte, 2008;Millet & Dewitte, 2009;Pearson & Schipper, 2012;Sanchez-Pages & Turiegano, 2010;Sapienza et al, 2009;Schipper, 2011a;Trahms et al, 2010;van den Bergh & Dewitte, 2006) Direct measures of hormones (saliva or blood samples) (N=11) (Apicella et al, 2008;Apicella et al, 2011;Burnham, 2007;Coates & Herbert, 2008;Sanchez-Pages & Turiegano, 2010;Sapienza et al, 2009;Schipper, 2011a;Schipper, 2011b;White et al, 2006;…”
Section: Discussionmentioning
confidence: 99%
“…Obviously the literature involves a wider variety of tasks and games including self-selection into competitive environments (Apicella et al, 2011;Buser, 2010;Wozniak et al, 2011), explorations of the Allais paradox (Da Silva et al, 2011), bidding behavior in auctions (Pearson & Schipper, 2012), decision making in trust, ultimatum, dictator, public good and prisoners' dilemma games (Burnham, 2007;Buser, 2011;Eisenegger et al, 2010;Kosfeld et al, 2005;Millet & Dewitte, 2006;Millet & Dewitte, 2009;Sanchez-Pages & Turiegano, 2010;van den Bergh & Dewitte, 2006;Zak et al, 2005a;Zak et al, 2005b;Zak et al, 2007;Zethraeus et al, 2009) as well as entrepreneurship decisions (White et al, 2006). A critical synthesis of the above mentioned studies that would explain differences in methods, findings etc.…”
Section: American Economic Review and Journal Of Risk And Uncertaintymentioning
confidence: 99%
“…Several studies have examined whether facial asymmetry is related to whether faces are rated as attractive by the subjects themselves or by other viewers, and some found a significant association [57,249,295,374], whereas others found no association [102,105] or a weak association only for male but not female faces [247]. Some analyses showed an association between fluctuating asymmetry and facial femininity or masculinity in humans [375], but others did not [102,374], nor was there a correlation between femininity or masculinity of skull shape and fluctuating asymmetry in baboons, chimpanzees, and gorillas [110]. Also, no correlation was found between facial fluctuating asymmetry and the ratio of second to fourth digits, which relates to prenatal exposure to sex hormones [375,376].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 99%
“…Some analyses showed an association between fluctuating asymmetry and facial femininity or masculinity in humans [375], but others did not [102,374], nor was there a correlation between femininity or masculinity of skull shape and fluctuating asymmetry in baboons, chimpanzees, and gorillas [110]. Also, no correlation was found between facial fluctuating asymmetry and the ratio of second to fourth digits, which relates to prenatal exposure to sex hormones [375,376]. By contrast, short-term effects of hormonal levels on asymmetry have been shown, as the asymmetry of facial shape changes during the menstrual cycle of individual women [294].…”
Section: Developmental Instability Of Shape In Relation To Stress Andmentioning
confidence: 99%
“…Price et al (2015) also found that men with more attractive bodies are less egalitarian on a variety of behavioural and psychological measures, but found no relationship between bodily formidability and these egalitarianism measures. Several experimental economic studies (Sanchez-Pages & Turiegano, 2010;Shinada & Yamagishi, 2014;Takahashi, Yamagishi, Tanida, Kiyonari, & Kanazawa, 2006;Zaatari & Trivers, 2007) have demonstrated that relatively inegalitarian resource distribution decisions are made by men who possess traits that are judged as more attractive by others, and/or who possess more symmetrical faces and bodies (symmetry being a putative indicator of attractiveness, health, and underlying genotypic quality [Møller, 2006]). Finally, Holtzman, Augustine, and Senne (2011) reported that bodily/facial symmetry relates negatively to prosocial personality traits, including some related to egalitarianism (e.g., fairness, empathy), in both men and women.…”
mentioning
confidence: 99%